ANALYSIS OF VILLAGE DEVELOPMENT BASED ON VILLAGE FUNDS (CASE STUDY OF SEI ROTAN VILLAGE, PERCUT SEI TUAN DISTRICT) - Mahyudin Situmeang (JURNAL GEOGRAFI, 2021)
So far, the government has realized the village fund budget every year. Therefore, every village government must develop plans that can support the community's welfare by prioritizing community priorities or needs. The purpose of this study was to analyze the village fund allocation policies in village development planning. This type of research is descriptive qualitative. Data collection techniques are carried out by observation and interviews, then analyzed using qualitative analysis techniques. Data processing is done by reducing, categorizing, and concluding, and presenting data. The results of this study found that so far, the village fund allocation policies have been implemented well, such as meeting basic needs, building facilities and infrastructure, developing local economic potential, and utilizing natural and environmental resources. Likewise, the face of the regional planning of Sei Rotan Village using the Village Fund budget has been able to leverage Village welfare. However, the problem is that the planned program has not been fully fulfilled due to limited human resources and funding. The regional development realized with village funds are roads, bridges, and drainage at flood-prone points. The land use pattern of the Sei Rotan area shows the expansion of the built-in land in the form of developer housing and community villages.Keywords: Village Fund, Development, TerritoryPemerintah sejauh ini telah merealisasikan anggaran dana desa setiap tahunnya. Oleh karena itu, setiap pemerintah desa wajib membuat perencanaan pembangunan yang dapat mendukung kesejahteraan masyarakat dengan mengutamakn perioritas atau kebutuhan masyarakat. Tujuan penelitian ini adalah untuk menganalisis kebijakan alokasi dana desa dalam perencanaa pembangunan wilayah desa. Jenis penelitian ini adalah deskriptif kualitatif. Tehnik pengumpulan data dilaksanakan dengan observasi dan wawancara, kemudian dianalisis menggunakan tehnik analisis kualitatif. Pengolahn data dilakukan dengan mereduksi, mengkategorisasikan, dan menyimpulkan dan menyajikan data. Hasil penelitian ini menemukan bahwa selama ini kebijakan alokasi dana desa telah dilaksanakan dengan baik seperti pemenuhan kebutuhan dasar, pembangunan sarana dan prasarana, pengembangan potensi ekonomi lokal, dan pemanfaatan sumber daya alam dan lingkungan. Demikian halnya wajah perencanaan wilayah Desa Sei Rotan dengan menggunakan anggaran Dana Desa telah mampu mengungkit peningkatan kesejahteraan Desa. Namun permasalahannya belum sepenuhnya program yang direncanakan terpenuhi dikarenakan keterbatasan sumberdaya manusia dan anggaran. Adapun pengembangan wilayah yang terealisasi dengan dana desa adalah pembangunan jalan, jembatan, drainase pada titik-titik rawan banjir. Pola pemanfaatan lahan kawasan Sei Rotan memperlihatkan perluasan lahan terbangun dalam wujud perumahan pengembang maupun perkampungan masyarakat.Kata kunci: Dana Desa, Pembangunan, Wilayah